2017
DOI: 10.1080/16546628.2017.1334484
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of the effects of consumption of ‘Yabukita’ or ‘Benifuuki’ encapsulated tea-powder on low-density lipoprotein cholesterol level and body weight

Abstract: Background: Previous studies have reported controversial results for the association between green tea consumption and low-density lipoprotein (LDL)-cholesterol and body weight. Objective: The objective of this trial was to determine the effects of two kinds of green tea on LDL-cholesterol and body weight. Methods: We randomly assigned 151 participants (98 men, 53 women) aged 30–70 years into three groups: Yabukita green tea group, Benifuuki green tea group, or placebo group. Participants consumed 1.8 g/day of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In all, the antagonistic effect of zinc selenium tea on a HSHF diet was pronounced. The results were in accordance with previous lipometabolism studies 27 29 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In all, the antagonistic effect of zinc selenium tea on a HSHF diet was pronounced. The results were in accordance with previous lipometabolism studies 27 29 .…”
Section: Discussionsupporting
confidence: 93%
“…In addition, in a randomized controlled trial, Yuko et al . (2017) demonstrated that Japanese green tea may lower low-density lipoprotein cholesterol, and the magnitude of the lipid-lowering effect of the tea was significantly larger than that of placebo 29 . In this study, we designed a HSHF diet animal group via mimicking human diet habits.…”
Section: Discussionmentioning
confidence: 99%
“…Benifuuki green tea, containing O-methylated catechin, was shown to remarkably reduce serum concentrations of LDL-C and lectin-like oxidized low-density lipoprotein receptor-1 ligands containing apolipoprotein B (LAB) in a randomized controlled trial (RCT) conducted on 155 volunteers [85]. Another RCT including 151 volunteer subjects also showed that Benifuuki and Yabukita green teas could decrease the LDL-C level [86]. In addition, consumption of green tea catechin extract for one year could lower serum TC ( p = 0.0004), LDL-C ( p < 0.0001), and non-HDL cholesterol ( p = 0.0032) in healthy postmenopausal women [26].…”
Section: Clinical Trailsmentioning
confidence: 99%
“…However, findings from randomized controlled trials (RCTs) on green tea supplementation and glycemic control or insulin sensitivity in individuals with preclinical diabetes or T2DM are debatable. Some studies observed that green tea significantly improve glycemic control [12], whereas others found no significant association between green tea intake and glycemic control [13,14].…”
Section: Introductionmentioning
confidence: 99%